Determination of Heavy Metals and Other Toxic Elements In Four Brands of Commercial Bottled Water From Indonesia Market By ICP/MS - Alam, Tunas (ALKIMIA, 2021)
Heavy metals and toxic elements four brands of commercial bottled water from Indonesia market were analyzed by using Inductive Couple Plasma-Mass Spectrometer (ICP-MS). The heavy metals and toxic elements to be analyzed were copper (Cu), iron (Fe), lead (Pb), cadmium (Cd), chromium (Cr), arsenic (As), selenium (Se) and manganese (Mn). The results are the heavy metals and toxic elements from all commercial water samples were below the permissible level of the World Health Organization (WHO) and Standar Nasional Indonesia (SNI). Hence, this determination clarify no risk about quality and safety of commercial bottled water for public drinking water.